2022
DOI: 10.1039/d2nr04600h
|View full text |Cite
|
Sign up to set email alerts
|

Combining surface chemical functionalization with introducing reactive oxygen species boosts ethanol electrooxidation

Abstract: The introduction of functional groups or oxygen vacancies into Pd-based electrocatalysts is a powerful strategy for enhancing those electrocatalytic performances toward many electrocatalytic reactions. Herein, an amorphous ceria-modified Pd nanocomposites...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[78] Ideal Pd-based catalysts, therefore, should have suitable binding energy with CH 3 CO and OH intermediates, which can be changed by the downshifted d-band center. For example, Zhao et al [79] combined a surface chemical functionalization with structure defect engineering to fabricate the Pd-CeO 2-x /FGS, serving the alkaline EOR electrocatalyst (Figure 4a,b). The obtained catalyst exhibited impressive mass activity (specific activity) of 1871.3 mA mg −1 (5.62 mA cm −2 ), being 4.78 (2.93) times enhancement versus the commercial Pd/C electrocatalyst.…”
Section: Pd-based Catalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…[78] Ideal Pd-based catalysts, therefore, should have suitable binding energy with CH 3 CO and OH intermediates, which can be changed by the downshifted d-band center. For example, Zhao et al [79] combined a surface chemical functionalization with structure defect engineering to fabricate the Pd-CeO 2-x /FGS, serving the alkaline EOR electrocatalyst (Figure 4a,b). The obtained catalyst exhibited impressive mass activity (specific activity) of 1871.3 mA mg −1 (5.62 mA cm −2 ), being 4.78 (2.93) times enhancement versus the commercial Pd/C electrocatalyst.…”
Section: Pd-based Catalystsmentioning
confidence: 99%
“…Due to the enhanced reaction kinetic, the optimal catalyst had mass activity up to 8452.8 mA mg Pd −1 , being a fivefold increase compared to the pure Pd. Recently, Yang et al [87] suggested the promoting effect of the Ni(OH) 2 on the EOR performance of Pd-based electrocatalysts by the formation of configuration between Pd and amorphous Ni(OH) 2 species, resulting in the optimization of the Pd─Pd interatomic distance and then the generation of the [79] Copyright 2022, Royal Society of Chemistry. c-e) Reproduced with permission.…”
Section: Pd-based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Platinum (Pt) and palladium (Pd) based noble metal catalysts have been widely used for anode alcohol oxidation reaction (AOR) in DAFCs, however, the unsatisfactory activity and poor stability have impeded their further application. [3][4][5][6] Hence, developing high-performance anodic AOR catalysts is of great importance for the widespread utilization of DAFCs.…”
Section: Introductionmentioning
confidence: 99%